Osmotic Demyelination Syndrome: A Case Report - Hoque, M Azizul; Haque, M Zahirul; Alam, ABM Saiful; Islam, AHM Tohurul; Rashid, DA; Hossain, M Jahangir (TAJ: Journal of Teachers Association, 2009)
We report a case of a middle aged lady who presented with alteration of consciousness and dysphasia. She was found to have hyponatremia which was corrected rapidly. After initial improvement, she subsequently developed marked deterioration of conscious level with upper motor sign signs in all four limbs. Osmotic demyelination syndrome was diagnosed by MRI. Severe hyponatremia carries a risk of cerebral edema with a significant mortality, but correcting it too rapidly can result in even more disastrous condition- osmotic demyelination syndrome. doi: 10.3329/taj.v21i2.3800 TAJ 2008; 21(2): 170-173